Acid flux-cored wire for X80 automatic welding, preparation method and ring welding joint

By filling the acidic flux-core welding wire for X80 automatic welding with oxides of specific components and optimizing the wire composition, the problem that the weld port performance in existing welding technology cannot reach the 0.254mm standard is solved, and the welding performance of high-steel oil and gas pipeline ring welds has been improved, meeting the requirements of the highest international standards.

CN119794649AActive Publication Date: 2025-04-11CHINA NAT PETROLEUM CORP +2
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202311303935.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-09
Publication Date
2025-04-11
Estimated Expiration
2043-10-09

AI Technical Summary

Technical Problem

In the existing welding technology, the weld performance cannot reach the standard value of 0.254mm, resulting in limited large-scale application of welding materials for high-steel oil and gas pipeline ring welds.

Method used

An acidic flux-core welding wire for X80 automatic welding was developed. By filling the flux-core in the steel strip, the flux-core contains oxides of specific components, the C, Mn, Si and Ni content of the welding wire is optimized, and the tensile strength and impact toughness of the welded metal are improved, ensuring that the CTOD value reaches or exceeds 0.254mm.

Benefits of technology

The welding performance of high-grade oil and gas pipeline ring welds with welding materials reaches the highest international standards, and meets the tensile strength, fracture toughness and impact toughness requirements of X80-grade pipeline steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004485506460000101
    Figure BDA0004485506460000101
  • Figure BDA0004485506460000102
    Figure BDA0004485506460000102
  • Figure BDA0004485506460000111
    Figure BDA0004485506460000111
Patent Text Reader

Abstract

The invention relates to the technical field of welding materials, in particular to an acidic flux-cored wire for X80 automatic welding, a preparation method and a ring welding joint, the acidic flux-cored wire for X80 automatic welding comprises a flux core and a steel strip, the flux core comprises, by mass, 4%-4.5% of SiO2, less than or equal to 7% of MgO, 15%-20% of MnO, 45%-55% of TiO2, 14%-20% of NiO, less than or equal to 3% of Na2O, less than or equal to 2% of Al2O3 and less than or equal to 3% of ZrO2; the steel strip comprises 0.02%-0.04% of C, 0.15%-0.35% of Mn, smaller than or equal to 0.03% of Si, smaller than or equal to 0.0015% of S, smaller than or equal to 0.015% of P, smaller than or equal to 0.05% of Al, smaller than or equal to 0.005% of N, smaller than or equal to 0.001% of B and the balance Fe. The optimal proportion of C, Mn, Si and Ni of the welding wire is selected by controlling the components of the steel strip and the flux core, the tensile strength, the elongation at break and the impact absorption rate of deposited metal are improved, the CTOD value influenced by the content of P and S is controlled, and the CTOD value meets the standard requirement of being larger than or equal to 0.254 mm. The problem that in the prior art, in the welding technology, the CTOD value cannot reach the 0.254 mm standard value on the welded junction performance requirement is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of welding materials, and in particular to an acid flux-cored welding wire for X80 automatic welding, a preparation method and a girth welding joint. Background Art

[0002] The development of welding materials is progressing with the development of industry. Long-distance oil and gas pipelines all use thick-walled and large-diameter steel pipes, and the strength of the steel pipes is guaranteed by a variety of alloy elements, organizational types and grain refinement. Solid wire gas shielded automatic welding and gas shielded flux-cored wire automatic welding are the development direction of large-diameter, thick-walled oil and gas pipeline welding. However, for this welding process, there is little research on the applicability of newly developed welding materials to the welding of thick-walled, high-grade pipeline steel pipes with different chemical compositions, which hinders the large-scale application of high-grade oil and gas pipeline girth weld welding materials.

[0003] At present, there are many welding construction standards required for external pipeline systems. However, no matter which welding construction standard is used, the requirements and acceptance standards for the tensile, impact, bending and notching hammer fracture of the weld are not much different. The number of tests for tensile and bending is determined according to different pipe diameters. The tensile acceptance index should be greater than or equal to the nominal minimum tensile strength of the pipe. When the pipe is broken in the parent material, the strength is not less than 95% of the nominal minimum tensile strength of the pipe, which is considered qualified. Taking X80 grade pipeline steel as an example, the impact toughness acceptance index meets the design requirements or the minimum average value is 40J, and the minimum single value is 30J. Regarding the acceptance value requirements of crack tip opening displacement (CTOD), there are only relevant requirements in AS2885.2 and DNVF101. The AS2885.2 standard requires that the results of the CTOD test should meet the average value of 0.15mm and the minimum value of 0.10mm. The DNVF101 standard needs to meet the design requirements, which is generally 0.15mm.

[0004] At present, the most stringent acceptance standard in the world is the CTOD acceptance value of 0.254mm as stipulated in DEC-NGP-G-WD-002-2020-1 "Technical Regulations for Welding of Oil and Gas Pipeline Engineering Lines". For the distribution trend of the CTOD value of the weld joint inspection of the gas shielded flux-cored welding wire currently used, see Figure 1 It can be seen that the CTOD values ​​of the welds for welding process assessment are basically between 0.10 and 0.213 mm. Only one sample has a test value of 0.261 mm, which meets the requirements. The CTOD tests of all welds cannot meet the standard requirement of 0.254 mm. It can be seen that the existing welding technology cannot meet the standard value of 0.254 mm in terms of weld performance requirements. Summary of the invention

[0005] Aiming at the problem that the welding technology in the prior art cannot meet the standard value of 0.254 mm in terms of weld performance requirements, the present invention provides an acid flux-cored welding wire for X80 automatic welding.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides an acidic flux-cored welding wire for X80 automatic welding, comprising a flux core and a steel strip, wherein the flux core is filled in the steel strip;

[0008] The core comprises the following components by mass percentage: 4% to 4.5% SiO2, ≤7% MgO, 15% to 20% MnO, 45% to 55% TiO2, 14% to 20% NiO, ≤3% Na2O, ≤2% Al2O3 and ≤3% ZrO2; the rest are CaO, K2O, CeO2, P2O5, Bi2O3, La2O3 and Nb2O5, and the sum of CaO, K2O, CeO2, P2O5, Bi2O3, La2O3 and Nb2O5 is ≤0.7%;

[0009] The steel strip comprises the following components by mass percentage:

[0010] 0.02% to 0.04% C, 0.15% to 0.35% Mn, ≤0.03% Si, ≤0.0015% S, ≤0.015% P, ≤0.05% Al, ≤0.005% N and ≤0.001% B, and the balance is Fe.

[0011] Preferably, the deposited metal components of the welding wire include, by mass percentage: 0.03% to 0.06% C, 1% to 1.7% Mn, 0.15 to 0.5% Si, S≤0.01%, and P≤0.012%.

[0012] Preferably, the deposited metal has a tensile strength of ≥674 MPa, a yield strength of ≥615 MPa, an elongation after fracture of ≥22%, an impact energy of 122 to 123 J at -20°C, and an impact energy of 81 to 109 J at -40°C.

[0013] Preferably, the steel strip has a tensile strength of 280-360 MPa, a yield strength of ≥140 MPa, an elongation of ≥38%, and a hardness of HRB ≥40.

[0014] Preferably, the steel belt is a U-shaped steel belt.

[0015] Preferably, the oil content of the steel strip is 0.2-0.5 g / 10 kg.

[0016] The method for preparing the above-mentioned acid flux-cored welding wire for X80 automatic welding comprises the following steps:

[0017] Mixing the raw material powders of the various components of the drug core uniformly according to the percentage of the raw material components to obtain a drug core mixed powder;

[0018] Prepare the steel strip and treat the surface of the steel strip;

[0019] Filling the flux core mixed powder into the steel strip to prepare a prefabricated welding wire;

[0020] The prefabricated welding wire is drawn and reduced in diameter to reach a target diameter, thereby obtaining an acid flux-cored welding wire.

[0021] Preferably, the prefabricated welding wire is drawn at a speed of 100±50 m / min.

[0022] A girth weld joint is formed by welding with the above-mentioned X80 automatic welding acid flux-cored wire.

[0023] Preferably, the tensile strength of the girth weld joint should be ≥625MPa; the fracture toughness test value of the weld and the heat-affected zone CTOD ≥0.254mm; the hardness value of the girth weld joint weld metal and the heat-affected zone root weld ≤300HV 10 , other positions ≤325HV 10 ; The Charpy impact toughness of the girth weld joint at -20℃ has a single value of ≥38J and an average value of ≥50J.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention discloses an acidic flux-cored welding wire for X80 automatic welding, comprising a flux core and a steel strip, wherein the flux core is filled in the steel strip;

[0026] The core comprises the following components by mass percentage: 4% to 4.5% SiO2, ≤7% MgO, 15% to 20% MnO, 45% to 55% TiO2, 14% to 20% NiO, ≤3% Na2O, ≤2% Al2O3 and ≤3% ZrO2;

[0027] The steel strip comprises the following components by mass percentage:

[0028] 0.02% to 0.04% C, 0.15% to 0.35% Mn, ≤0.03% Si, ≤0.0015% S, ≤0.015% P, ≤0.05% Al, ≤0.005% N and ≤0.001% B, and the balance is Fe.

[0029] The flux system of this welding wire is TiO2-MnO-NiO-Fe2O3-MgO-SiO2. By controlling the components of the steel strip and the flux core, the optimal ratio of the C, Mn, Si and Ni content of the entire welding wire is selected, thereby improving the tensile strength, elongation at break and impact absorption rate of the deposited metal. The content of P and S is further controlled to affect the CTOD value, so that the CTOD value meets the standard requirement of ≥0.254mm. After testing, the weld properties of the weld metal, weld and other welds of this welding wire all meet the current highest international requirements.

[0030] The C content in the deposited metal is set between 0.030% and 0.060%. A C content less than 0.030% cannot meet the strength requirements of the deposit and process joints. If the C content is greater than 0.060%, the tensile strength of the deposited metal is likely to be higher than 690MPa, affecting the elongation after fracture, impact absorption capacity and CTOD value of the deposited metal and process joints; the Mn content is set at 1.00% to 1.70%, the Si content is set at 0.15% to 0.50%, and the Ni content is designed at 1.5 to 2.0%. This combination can obtain good impact performance, elongation and CTOD value; P≤0.012%, S≤0.010%, high content of P and S will reduce the low-temperature impact value, increase the brittle temperature, and thus affect the CTOD value.

[0031] The present invention also provides a method for preparing an acidic flux-cored welding wire for automatic welding such as X80. The method comprises the following steps: uniformly mixing raw material powders of various components of the flux core according to the percentage of raw material components to obtain a flux core mixed powder; preparing a steel strip and treating the surface of the steel strip; filling the flux core mixed powder into the steel strip to prepare a prefabricated welding wire; drawing and reducing the prefabricated welding wire to make the prefabricated welding wire reach a target diameter to obtain an acidic flux-cored welding wire. The preparation method is simple and easy to industrialize.

[0032] The present invention also provides a girth weld joint, which is welded by the above-mentioned X80 automatic welding acid flux-cored wire, and the tensile strength of the girth weld joint should be ≥625MPa; the fracture toughness test value CTOD of the weld and the heat-affected zone should be ≥0.254mm; the hardness value of the weld metal and the heat-affected zone of the girth weld joint root welding should be ≤300HV 10 , other positions ≤325HV 10 The Charpy impact toughness of the girth weld joint at -20℃ is ≥38J and the average is ≥50J, meeting the highest international standards. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a distribution trend diagram of the CTOD value of the weld detection of the gas shielded flux-cored welding wire used in the prior art of the present invention.

[0034] Figure 2 The present invention is a flow chart of a method for preparing an acidic flux-cored welding wire for X80 automatic welding.

[0035] Figure 3 This is a macroscopic view of the girth weld after welding using the acid flux-cored wire for X80 automatic welding according to the present invention.

[0036] Figure 4 This is a sampling diagram for testing the mechanical properties of the girth weld after welding using the acidic flux-cored wire for X80 automatic welding of the present invention.

[0037] Figure 5 This is a tensile stress-strain curve diagram of the girth weld after welding using the acid flux-cored wire for X80 automatic welding of the present invention, wherein a is a tensile stress-strain curve diagram of the entire weld numbered T0-WM, and b is a tensile stress-strain curve diagram of the entire weld numbered T6-WM.

[0038] Figure 6 This is a diagram of the indentation position of the circumferential weld sampled after welding using the acid flux-cored wire for X80 automatic welding according to the present invention.

[0039] Figure 7 This is a macroscopic morphology of the ring weld sampled after welding using the acid flux-cored wire for X80 automatic welding of the present invention, wherein a is the macroscopic morphology of the weld in the M0 flat welding position, b is the macroscopic morphology of the weld in the M3 vertical welding position, and c is the macroscopic morphology of the weld in the M6 ​​overhead welding position.

[0040] Figure 8 This is a flat weld after welding using the acid flux-cored wire for X80 automatic welding of the present invention, wherein a is the stress loading and crack tip angular displacement diagram of the CTOD test of D0-WM, and b is the weld fracture morphology after the CTOD test.

[0041] Fig. 9 This is the heat affected zone of the flat welding position weld after welding using the acid flux-cored wire for X80 automatic welding of the present invention, wherein a is the stress loading and crack tip angular displacement diagram of the CTOD test of D0-HAZ, and b is the fracture morphology of the heat affected zone of the weld after the CTOD test.

[0042] Fig.10 This is a vertical weld after welding using the acid flux-cored wire for X80 automatic welding of the present invention, wherein a is the stress loading and crack tip angular displacement diagram of the CTOD test of D3-WM, and b is the weld fracture morphology after the CTOD test.

[0043] Fig.11 This is the heat affected zone of the vertical welding ring weld after welding with the acid flux-cored wire for X80 automatic welding of the present invention, wherein a is the stress loading and crack tip angular displacement diagram of the CTOD test of D3-HAZ, and b is the fracture morphology of the weld heat affected zone after the CTOD test.

[0044] Fig.12This is a backward tilted weld welded by using X80 automatic welding acid flux-cored wire according to the present invention. a is a stress loading and crack tip angular displacement diagram of a CTOD test of D6-WM, and b is a weld fracture morphology diagram after the CTOD test.

[0045] Fig.13 This is the heat affected zone of the weld in the backward tilt position welded by the acid flux-cored wire for X80 automatic welding of the present invention, wherein a is the stress loading and crack tip angular displacement diagram of the CTOD test of D6-HAZ, and b is the fracture morphology of the weld heat affected zone after the CTOD test. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0047] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.

[0049] In the description of the embodiments of the present invention, it should be noted that if the terms "upper", "lower", "horizontal", "inner", etc. indicate an orientation or positional relationship based on the orientation or positional relationship shown in the drawings, or the orientation or positional relationship in which the product of the invention is usually placed when in use, it is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In addition, the terms "first", "second", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.

[0050] In addition, if the term "horizontal" appears, it does not mean that the component is required to be absolutely horizontal, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", which does not mean that the structure must be completely horizontal, but can be slightly tilted.

[0051] In the description of the embodiments of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal connection of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0052] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0053] The present invention provides an acidic flux-cored welding wire for X80 automatic welding, comprising a flux core and a steel strip, wherein the flux core is filled in the steel strip;

[0054] The core comprises the following components by mass percentage: 4% to 4.5% SiO2, ≤7% MgO, 15% to 20% MnO, 45% to 55% TiO2, 14% to 20% NiO, ≤3% Na2O, ≤2% Al2O3 and ≤3% ZrO2;

[0055] The steel strip comprises the following components by mass percentage:

[0056] 0.02% to 0.04% C, 0.15% to 0.35% Mn, ≤0.03% Si, ≤0.0015% S, ≤0.015% P, ≤0.05% Al, ≤0.005% N and ≤0.001% B, and the balance is Fe.

[0057] Calculated by mass percentage, the deposited metal composition of the welding wire is: 0.03% to 0.06% C, 1% to 1.7% Mn, 0.15 to 0.5% Si, S < 0.01%, and P < 0.012%.

[0058] The deposited metal has a tensile strength greater than 674 MPa, a yield strength greater than 615 MPa, an elongation after fracture greater than 22%, an impact energy of 122 to 123 J at -20°C, and an impact energy of 81 to 109 J at -40°C.

[0059] The composition system TiO2-MnO-NiO-MgO-Al2O3-SiO2 powder and steel strip components are key factors to ensure the performance of girth weld and excellent welding processability. The total amount of TiO2-MnO-NiO-MgO-Al2O3-SiO2 in the composition system does not exceed 95%; MgO+Na2O≤8.3%; trace oxides are residues in minerals, with a total amount of ≤0.7%;

[0060] Preferably, the steel belt is a U-shaped steel belt, and the oil content of the steel belt is 0.2-0.5 g / 10 kg.

[0061] See also Figure 2 The present invention also provides a method for preparing the above-mentioned X80 acid flux-cored welding wire for automatic welding, comprising the following steps:

[0062] S1: Mix the raw material powders of the core components uniformly according to the percentage of the raw material components to obtain the core mixed powder; according to the mechanical properties and diffusible hydrogen content requirements of the deposited metal of the welding wire, the requirements of GB / T 36233-2018 "High-strength Steel Flux-cored Welding Wire", the mechanical properties of the girth weld joint welded with this welding wire meet the requirements of DEC-NGP-G-WD-002-2020-1 "Technical Regulations for Welding of Oil and Gas Pipeline Engineering Lines", to determine the design and optimization of the composition system of the powder in the flux-cored welding wire, and further analyze the influence of welding process parameters on the process performance of the welding wire during on-site combined automatic welding, such as welding spatter, molten iron fluidity and spreadability, droplet transition form, slag removal, etc., and slightly adjust the alloy composition of the flux core so that the flux core includes 4% to 4.5% SiO2, ≤7% MgO, 15% to 20% MnO, 45% to 55% TiO2, 14% to 20% NiO, ≤3% Na2O, ≤2% Al2O3 and ≤3% ZrO2 by mass percentage;.

[0063] S2: Prepare the steel strip and treat the surface of the steel strip; according to the provisions of GB / T 36233-2018 "High Strength Steel Flux-Cored Welding Wire", ensure the requirements for the content of diffusible hydrogen in the deposited metal and the wire feeding stability of the welding wire, specify the steel strip process required for the production of acid flux-cored welding wire, and perform process control of the surface treatment of the steel strip and the amount of oil; this application adopts SPCC cold-rolled bright steel strip for production. And the protective oil content and cleaning conditions on the surface of the steel strip are limited. After the welding flux stirring and steel strip rewinding process, the welding wire is formed and produced. The steel strip is a U-shaped steel strip, and the oil content of the steel strip is 0.2-0.5g / 10Kg.

[0064] S3: Fill the flux core mixed powder into the steel strip to prepare the prefabricated welding wire; remove the crystal water from the welding wire flux core and mix it evenly to achieve the target particle size of the flux core mixed powder, add the flux core mixed powder into the U-shaped groove of the steel strip through the powder feeder, and control the filling ratio of the flux core mixed powder in the steel strip between the standard value of 13%-15% as needed, and control the filling ratio deviation within ±0.6% of the standard value. The filling ratio target value is 14%, and the deviation is: ±0.6%.

[0065] S4: The prefabricated welding wire is drawn and reduced to reach the target diameter to obtain the acidic flux-cored welding wire; the wire drawing process is strictly controlled, the welding wire specifications are stable, and the deviation range of the welding wire diameter and the standard wire diameter is required to be -0.03mm to -0.01mm. The prefabricated welding wire is drawn at a speed of 100±50m / min. Continue the drawing process of the high-strength straight-feed wire drawing machine. The fine drawing of the flux-cored welding wire is achieved by drawing the wire drawing die on the production line. Each deformation drawing of the cross-sectional diameter size passes through the wire drawing die hole of a certain shape and size, and finally reaches the required diameter size of the finished product. The wire diameter is strictly controlled, and the wire diameter is installed with online real-time monitoring equipment to ensure stable quality. The fine drawing line speed is ≤1500m / min, and the oil content value is specified in the range of 0.2~1.0g / 10kg. Specifically, the prefabricated welding wire is wound onto the wire reel according to a certain weight. The winding link mainly relies on the linear adjustment of the welding wire to improve the wire feeding performance. During the coiling process, the wire pressing wheels acting in different directions can adjust the relaxation diameter and pitch while eliminating the internal stress of the welding wire. The appropriate relaxation diameter and pitch can reduce the resistance of the welding wire passing through the wire feeding tube, thereby ensuring the consistency of the wire feeding, which is used for on-site welding test. Welding is carried out according to the on-site combined automatic welding process regulations. After the on-site welding process test and weld joint mechanical property test meet the requirements, the X80 fully automatic acid cored welding wire based on stress design with welding process and weld joint performance meeting the requirements is obtained.

[0066] When in use, test welding is carried out according to the existing on-site welding process regulations to adjust the welding process parameters of the on-site combined automatic welding equipment, and then continuous welding of the weld joint is carried out, and the welding process parameters such as welding current, welding voltage, wire feeding speed, dwell time, gas flow rate and welding heat input are adjusted. When automatic welding is carried out, the welding processability of the welding wire is evaluated, including: arc stability, droplet transition state, molten pool fluidity, spatter, slag removal, etc. After the test ring weld is welded and the non-destructive testing is qualified, the transverse and longitudinal tensile, side bending, hardness, metallographic, notch hammer breaking and impact toughness specimens at different positions, CTOD specimens are cut and machined. The tensile properties of the transverse plate specimens of the ring weld are tested. The fracture position is recorded. If the fracture is on the parent material, the tensile strength is greater than or equal to 95% of the nominal strength of the pipe, and it is judged to be qualified. If the fracture is on the weld, the tensile strength is greater than or equal to the nominal strength of the pipe and it is judged to be qualified.

[0067] After the combined automatic welding is performed, the welding process is evaluated, and the performance indicators that the weld meets are as follows: the tensile strength of the girth weld joint should not be less than 625MPa, and the tensile strength of the weld round bar specimen is equivalent to the strength of the pipe; the fracture toughness test value of the weld and the heat-affected zone, i.e. the crack tip displacement (CTOD), meets the requirement of ≥0.254mm, and the CTOD specimen is prepared and tested according to GB / T 21143, and the test results are calculated according to GB / T 28896; the hardness value of the girth weld joint weld metal and the heat-affected zone root weld is not more than 300HV 10 , other parts are not more than 325HV 10 ; The single value of Charpy impact toughness of girth weld joint at -20℃ should not be less than 38J, and the average value should not be less than 50J.

[0068] The present invention provides a girth weld joint, which is welded by using the above-mentioned X80 automatic welding acid flux-cored wire. The tensile strength of the girth weld joint should be ≥625MPa; the fracture toughness test value CTOD of the weld and the heat-affected zone should be ≥0.254mm; the hardness value of the weld metal and the heat-affected zone of the girth weld joint root welding should be ≤300HV 10 , other parts are not more than 325HV 10 ; The Charpy impact toughness of the girth weld joint at -20℃ has a single value of ≥38J and an average value of ≥50J.

[0069] Example

[0070] Taking the stress-based design of the X80 domestically produced acid flux-cored welding wire for automatic welding provided by the present invention for on-site welding of the X80 pipeline project, the composition and performance of the deposited metal of the welding wire, the process performance of on-site welding, and the mechanical properties test of the completed weld as an example for analysis;

[0071] First, the powder is mixed according to the proportion of the core ingredients to obtain the core mixed powder. The core ingredients are shown in the following table:

[0072]

[0073] Then, the steel strip is cut and wound again according to the requirements, and the powder feeder fills the mixed powder of the flux core into the steel strip rolled into a U-shaped groove by the forming machine, and then draws it. Finally, the X80 fully automatic acid flux-cored welding wire for stress-based design that meets the requirements is obtained.

[0074] The prepared welding wire was subjected to a deposited metal performance test, and the test results and standards are shown in the following table:

[0075]

[0076] It can be seen that the deposited metal composition of the X80 acid flux-cored welding wire for automatic welding prepared in this application is better than the current standard specified value.

[0077] The yield strength, tensile strength and -40°C Charpy impact performance tests were performed on the deposited metal of the X80 acidic flux-cored welding wire for automatic welding prepared in this application. The test results and standard values ​​are shown in the following table:

[0078]

[0079] It can be seen that the mechanical properties of the deposited metal are also better than the values ​​specified in the standard.

[0080] See also Figure 3 The ring weld welded by the welding wire produced by this invention patent has a beautiful weld surface, small welding spatter, no large particles of molten metal spatter, and the weld excess height is evenly distributed over the entire weld, indicating that the process parameters of the welding wire during the welding process are stable, the wire feeding speed is stable, and it has excellent welding processability.

[0081] After the deposited metal test is qualified, the on-site automatic welding test is carried out. The macroscopic image of the girth weld after welding shows that the pipes that are girth welded in all positions using the X80 automatic welding acid flux-cored wire have uniform weld shape, beautiful weld surface, good slag removal during welding, and small spatter, indicating that the product has good welding process performance. The appearance process evaluation indicators are shown in the table below:

[0082]

[0083] It can be seen that the appearance after welding is good and meets the appearance requirements of welding.

[0084] After welding, the weld is subjected to nondestructive testing, and after nondestructive testing, mechanical properties testing is performed. Figure 4 , the sampling diagram of mechanical test is used for sampling, and the tensile, impact, bending, notch hammer fracture, hardness, metallographic and CTOD tests are carried out at different welding positions of the weld to test the mechanical properties of the weld and check its welding processability. The tensile test is based on the standard GB / T228.1-2021, and the tensile strength test results are shown in the following table:

[0085]

[0086] In the table, T0-WM and T6-WM are full weld specimens, and T1, T2, T3 and T4 are welded joint specimens. Figure 5From the stress-strain curve of the full weld longitudinal tensile specimen, it can be seen that the yield strength of the weld metal reaches 620MPa~650MPa, the tensile strength reaches 641MPa~677MPa, and the uniform elongation is 26.5%~28.0%, which all meet the requirements of DEC-NGP-G-WD-002-2020-1 "Technical Regulations for Welding of Oil and Gas Pipeline Engineering Lines" and have very good tensile properties. The transverse tensile strength of its girth weld joint reaches 662MPa~688MPa, achieving equal strength matching connection with X80 grade pipeline steel, and meeting the tensile strength DEC standard requirements of X80 grade girth welds.

[0087] For the Charpy impact test, the welding wire prepared in this application is used for welding, and the weld joint is sampled after welding. The sampling number is based on the standard GB / T 229-2020. The experimental results are shown in the following table:

[0088]

[0089]

[0090] The weld joints after welding were sampled and numbered, and the notch hammer fracture test was carried out according to the standard GB / T 31032-2014. The test results are shown in the following table:

[0091]

[0092] The samples are numbered and subjected to guided bending tests according to the standard: GB / T2653-2008. The test results are shown in the following table:

[0093]

[0094]

[0095] See also Figure 6 According to the indentation position, the Vickers hardness test is carried out, and the hardness value is 211HV 10 ~245HV 10 The hardness distribution of the overall girth weld is stable, and there is no high hardness point, which indicates that the heat input temperature during the welding process of the weld is high and the organization of the girth weld is uniform. The test results are shown in the following table:

[0096]

[0097] The samples were numbered and radial analysis was performed on samples with different numbers. The analysis results are shown in Figure 7 It can be seen that the number of welding layers at different positions of the weld is consistent, the weld layer is clear, and there are no welding defects, indicating that the welding wire has good welding processability.

[0098] The results of low-power inspection of welds are shown in the following table:

[0099]

[0100] From the above mechanical properties test results, it can be seen that the mechanical properties of the welding wire prepared by the present application after welding are better than the standard value. It can be seen that the welds welded by the welding wire prepared by the present application have excellent strengthening and toughening properties.

[0101] Yield strength R of the sample material at the test temperature p0.2 =744MPa; tensile strength R m =807MPa, Poisson's ratio is taken as 0.3 during the calculation process, and the elastic modulus E=210GPa.

[0102] Take one specimen from each of the weld and heat-affected zone at the flat welding position, vertical welding position and overhead welding position of the weld, and the specimen numbers are D0-WM, D0-HAZ, D3-WM, D3-HAZ, D6-WM and D6-HAZ. The specimen is a three-point bending specimen with a nominal size of W = 36mm and B = 18mm. An integral knife-edge specimen is used, i.e. Z = 0. The prefabricated fatigue crack data is shown in the following table:

[0103]

[0104] The test was conducted according to the standard GB / T21143-2014, with a loading speed of 1mm / min. The COD gauge model for monitoring the crack mouth opening displacement was 3541-005M-100M-ST. The crack length was measured using a fracture analyzer with a measurement accuracy of 0.001mm. The crack size test results are shown in the following table:

[0105]

[0106] The results of the CTOD test are shown in the following table:

[0107]

[0108]

[0109] The results of the validation of the CTOD test results are shown in the following table:

[0110] Serial number Judgment content Is it satisfied? 1 The specimen shall meet the requirements of 5.4.1 for dimensions and errors; satisfy 2 The test device shall meet the requirements of 5.7 for error and coaxiality; satisfy 3 The testing machine and extensometer shall meet the accuracy requirements of 5.6; satisfy 4 <![CDATA[The average initial crack length a0 should be between 0.45W and 0.7W;]]> satisfy 5 The length of the prefabricated fatigue crack should not be less than 1.3mm or 2.5%W, whichever is greater; satisfy 6 The fatigue pre-cracks on both surfaces of the specimen should be within the envelope; satisfy 7 The stress intensity factor of prefabricated fatigue cracks shall meet the requirements of 5.4.2.4; satisfy 8 <![CDATA[The difference between the initial crack length at the middle seven points and the average value of the initial cracks at the nine points should not exceed 0.10a0;]]> satisfy 9 The initial slope of the force-displacement record should be between 0.85 and 1.5; satisfy

[0111] Combination Figures 8 to 13, the stress loading and crack tip angular displacement diagram (a) of the weld and heat-affected zone in the CTOD test at different welding positions (0-point flat welding, 3-point vertical welding and 6-point overhead welding) and the fracture morphology after the CTOD test show that the CTOD values ​​of the weld and heat-affected zone calculated according to GB / T 28896 are both >0.254mm, with good fracture toughness and crack propagation prevention performance. The above is only a preferred embodiment of the present invention and is not intended to limit the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principle of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. An acid flux-cored wire for X80 automatic welding, characterized in that: It comprises a core and a steel belt, wherein the core is filled in the steel belt; The core comprises the following components by mass percentage: 4% to 4.5% SiO2, ≤7% MgO, 15% to 20% MnO, 45% to 55% TiO2, 14% to 20% NiO, ≤3% Na2O, ≤2% Al2O3 and ≤3% ZrO2; the rest are CaO, K2O, CeO2, P2O5, Bi2O3, La2O3 and Nb2O5, and the sum of CaO, K2O, CeO2, P2O5, Bi2O3, La2O3 and Nb2O5 is ≤0.7%; The steel strip comprises the following components by mass percentage: 0.02% to 0.04% C, 0.15% to 0.35% Mn, ≤0.03% Si, ≤0.0015% S, ≤0.015% P, ≤0.05% Al, ≤0.005% N and ≤0.001% B, and the balance is Fe.

2. The X80 acid flux-cored welding wire for automatic welding according to claim 1, characterized in that: Measured by mass percentage, the deposited metal components of the welding wire include: 0.03% to 0.06% C, 1% to 1.7% Mn, 0.15 to 0.5% Si, S≤0.01%, and P≤0.012%.

3. The X80 acid flux-cored welding wire for automatic welding according to claim 2, characterized in that: The deposited metal has a tensile strength of ≥674MPa, a yield strength of ≥615MPa, an elongation after fracture of ≥22%, an impact energy of 122-123J at -20°C, and an impact energy of 81-109J at -40°C.

4. The X80 acid flux-cored welding wire for automatic welding according to claim 1, characterized in that: The steel strip has a tensile strength of 280-360 MPa, a yield strength of ≥140 MPa, an elongation of ≥38%, and a hardness of HRB ≥40.

5. The X80 acid flux-cored welding wire for automatic welding according to claim 1, characterized in that: The steel belt is a U-shaped steel belt.

6. The X80 acid flux-cored welding wire for automatic welding according to any one of claims 1 to 5, characterized in that: The steel strip oil content is 0.2-0.5 g / 10 kg.

7. The method for preparing the X80 acid flux-cored welding wire for automatic welding according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mixing the raw material powders of the components of the core uniformly according to the percentage of the raw material components to obtain a core mixed powder; Prepare the steel strip and treat the surface of the steel strip; Filling the flux core mixed powder into the steel strip to prepare a prefabricated welding wire; The prefabricated welding wire is drawn and reduced in diameter to reach a target diameter, thereby obtaining an acid flux-cored welding wire.

8. The method for preparing the X80 acid flux-cored welding wire for automatic welding according to claim 7, characterized in that: The prefabricated welding wire is drawn at a speed of 100±50m / min.

9. A girth weld joint, characterized in that: The welding method is carried out by using the X80 acid flux-cored welding wire for automatic welding as described in any one of claims 1 to 6.

10. The girth weld joint according to claim 9, characterized in that: The tensile strength of the girth weld joint should be ≥625MPa; the fracture toughness test value of the weld and heat-affected zone CTOD ≥0.254mm; the hardness value of the girth weld joint weld metal and heat-affected zone root weld ≤300HV 10 , other positions ≤325HV 10 ; The Charpy impact toughness of the girth weld joint at -20℃ has a single value of ≥38J and an average value of ≥50J.

Citation Information

Patent Citations

  • Gas-shielded flux-cored wire with recyclable welding slag

    CN102139424A

  • Gas shielded welding wire for high-strength coiled tubing

    CN108857137A

  • Flux-cored wire for high heat input welding and preparation method and application thereof

    CN109530961A

  • Stainless steel argon tungsten-arc welding active agent and preparation method and application thereof

    CN111604618A

  • Metal powder type flux-cored wire and preparation method and application thereof

    CN114161024A